Acute limb ischemia due to severe heparin-included thrombocytopenia with thrombosis during puerperium. Issue 2 (February 2023) - Noto, Tatsunori; Anzai, Hitoshi; Nemoto, Naohiko; Takenaka, Hiroki; Sahara, Naohiko; Shimizu, Takayuki; Yaguchi, Tomoyuki; Takaesu, Satoru; Samejima, Yusuke
Abstract: We present the case of a 39-year-old pregnant woman who had intrauterine fetal death and imminent uterine rupture and underwent cesarean section. She also underwent catheter embolization for hemorrhagic shock due to bleeding from the uterine artery, and heparin-containing saline was used. On day 7 of hospitalization, she felt severe pain in her right lower leg, and computed tomography (CT) revealed focal nonocclusive thrombus formations in the right common and external iliac artery. After intravenous heparin administration, she suddenly developed dyspnea, her blood pressure dropped, and her platelet count decreased. We diagnosed her with heparin-induced thrombocytopenia (HIT). Although we discontinued heparin and switched to argatroban, CT after 5 days revealed subtotal occlusion of the right iliac artery by a massive thrombus. We performed surgical thrombectomy using a Fogarty catheter, but blood flow was not restored. Therefore, we administered urokinase continuously with catheter-directed thrombolysis (CDT). The thrombus in the iliac artery gradually cleared and was successfully eliminated. However, the patient developed gangrene in her right lower leg, and we decided to perform an above-knee amputation of the right leg. She was discharged with a prosthetic leg and prescribed 15 mg of rivaroxaban per day. Learning objective: HIT is a known serious side effect of heparin administration, and it can sometimes be fatal. HIT treatment using aggressive thrombectomy procedures may be ineffective since such procedures may accelerate thrombus formation when the coagulation cascade is highly activated. In this case, CDT may have to be considered as the first-line treatment before Fogarty thrombectomy when argatroban therapy fails.